The changing relationship between affordability and house prices: A cross-country examination - Kieran McQuinn (The Economic and Social Research Institute (ESRI), 2017)
The recent increase in house prices across the OECD highlights again the importance of understanding the different determinants of residential property demand. Sustained activity in housing markets across a number of countries was one of the contributing factors to the financial sector vulnerabilities underpinning the crisis of 2007/2008. While much of the increases in prices observed was due to changes in key economic variables such as income levels and interest rates, it is apparent that actual price movements in the period leading up to 2007 were often in excess of what underlying economic conditions might have suggested. In this paper we apply a theoretical model of house price determination that is driven by changes in income, interest rates and, which crucially allows for changes in the relationship between these variables and house prices through time. Allowing for this complexity in the relationship between fundamental economic variables and house prices is particularly important, not least in facilitating more efficient implementation of both monetary and macroprudential policy in international housing markets.
Keywords: R21; R31; G12; 330; House Prices; Affordability; Credit